Glass-like thermal conductivity in mass-disordered high-entropy (Y, Yb)2(Ti, Zr, Hf)2O7 for thermal barrier material. (15th November 2021) - Song, Dowon; Song, Taeseup; Paik, Ungyu; Lyu, Guanlin; Jung, Yeon-Gil; Jeon, Hak-Beom; Oh, Yoon-Suk
Graphical abstract: Highlights: A novel high-entropy oxide (YYHEO) was engineered with significant mass disorder. YYHEO exhibited glass-like low thermal conductivity (1.27 W/m∙K). YYHEO exceeded typical substitutional solid solubility limit even with a significant atomic size difference (>50%). YYHEO shows thermal stability even at elevated temperature (1500  ° C) without any phase degradation. Thermophysical properties were compatible with YSZ (CTE: 10.08 × 10 −6 K −1, E : 218.21 ± 3.64 GPa and H : 14.42 ± 0.5 GPa). Abstract: An entropy-stabilization strategy was applied to engineer a novel thermal insulating material by establishing a single-phase solid solution with the formula of (Y1/2 Yb1/2 )2 (Ti1/3 Zr1/3 Hf1/3 )2 O7 (YYHEO). Structural analysis revealed that this material exceeded the typical substitutional solubility limit, even with a significant atomic size difference, where the conventional determination rule was defied. YYHEO exhibited a lower glass-like thermal conductivity due to its highly disordered crystal structure and the specific design strategy. The coefficient of thermal expansion and mechanical properties (e.g. elastic modulus and hardness) were comparable to conventional materials, suggesting that YYHEO is a promising candidate for application as a new thermal insulating material.